A COUPLED DYNAMIC FINITE ELEMENT ANALYSIS OF SATURATED SANDS (Journal of Engineering, 2024)
A general mixed finite element formulation (u - w - ) is presented in this paper. This formulation includes the inertia effects and the soil skeleton is considered compressible. The application of this formulation in solving soil dynamic problems of saturated sand is made by governing the boundary conditions concerning the pore fluid pressure. A problem of soil column subjected to an instantly applied surface loal is solved. The solid skeleton and pore fluid pressure are each modelled with ten 4- noded isoparametric elements. The results are compared with those obtained by Zienkiewic z et al. (1988)' It is concluded that the undamped response of displacement and pore pressure oscillates significantly with the increase of time step lenght.